Risk factors for the mortality of hemodialysis patients with COVID-19 in northern Hunan province, China - Zhangxiu He; Zhong Peng; Ning Gao; Shuzhu Zhong; Fengyi Yu; Zixu Tang; Zihao Liao; Song Zhao; Gloria Umwiza; Ming Chen; Wei Long (BMC Nephrology)
Abstract Purpose Exploring the risk factors for mortality of hemodialysis patients undergoing COVID-19 and the changes in mortality before and after the opening of the epidemic in northern Hunan province, China. Methods We analyzed 230 hemodialysis patients with COVID-19 in the Yiyang Central Hospital from November 01, 2022 to February 28, 2023. Demographic data, laboratory data and public diseases were collected. Cox regression analysis was used to identify risk factors and independent predictors of mortality. The receiver operating characteristic (ROC) curve was used to determine the diagnostic value of risk factors in hemodialysis COVID-19 patients. Results The average duration of the disease was 12.53 days. The mortality rate in our cohort was 28.70%. Independent predictors of mortality in our cohort were: age (hazard ratio [HR] 1.09; 95% confidence interval [CI], 1.05–1.14; P < 0.001), elevated procalcitonin (PCT) levels (HR 1.02; 95%CI, 1.01–1.03; P < 0.001), and higher white blood cell-neutrophil ratio (NWR) (HR 1.04; 95%CI, 1.04–1.07; P = 0.004). Areas under the ROC curve (AUC) for age, NWR, PCT, age*NWR were 0.70 (95%CI: 0.62–0.77), 0.82 (95%CI: 0.75–0.90), 0.64 (95%CI: 0.55–0.73), and 0.89 (0.85,0.94). Conclusion We discovered that old age, high levels of NWR and PCT might be predictors of mortality, reported the causes and prognostic predictors of mortality in hemodialysis populations with COVID-19 from northern Hunan, China.